Evaluation of National Institute of Justice-Funded Geospatial Software Tools Technical and Utility Assessments to Improve Tool Development, Dissemination, and Usage - Wong, Carolyn (RAND Corporation, 2014)
A geospatial software tool-evaluation study conducted for the National Institute of Justice (NIJ) assessed 14 recent NIJ-funded tool developments. The study integrates input from tool developers and users with RAND's independent assessments. The authors found that 12 developments resulted in fully functional tools and make five recommendations that will enable NIJ to maximize benefits to the law enforcement community from future developments.